Real-World Data on Metastatic Lung Cancer: Cost Analyses in Brazil From a Private Insurance Company's Perspective - Rodrigo Afonso da Silva Sardenberg; Mariana Ribeiro Monteiro; Cinthia Leite Frizzera Borges Bognar; Victor Braga Gondim Teixeira; Rodrigo de Carvalho Moreira; Henry Sznejder; Riad Naim Younes (JCO Global Oncology)
PURPOSENon–small cell lung cancer (NSCLC) is often diagnosed at late stages, leading to escalated treatment expenses. This study aimed to elucidate the costs of lung cancer treatment in a private health care setting in Brazil.MATERIALS AND METHODSWe conducted a retrospective cohort study, regarding costs, survival, and quality of care of stage IV NSCLC in a private health company in Brazil.RESULTSA total of 819 individuals were included, with median age 64.9 years. With a 1-year follow-up, patients had a median of four hospital admissions, with a median length of stay in of 6.2 days. Survival rates were higher for patients treated with targeted therapy (hazard ratio [HR], 0.38 [95% CI, 0.25 to 0.56]), immunotherapy (HR, 0.52 [95% CI, 0.40 to 0.68]), or both treatments sequentially (0.41 [95% CI, 0.25 to 0.68]). Patients submitted to sequentially targeted therapy and immunotherapy had the higher total costs (mean, $172,828 USD) compared with patients treated with immunotherapy (mean, $138,125 USD), targeted therapy (mean, $117,068 USD), and only chemotherapy (mean, $47,625 USD). As expected, longer survival was translated into more third-line therapy (P < .001), and higher mean costs with cancer-related hospital admissions ($24,554 USD chemo, $31,835 USD immuno, $28,228 USD targeted, and $35,494 USD for both therapies). However, costs did not increase in proportion to the survival benefit. Despite longer survival, patients undergoing targeted therapy or immunotherapy had median number of hospital admissions and length of stay similar to those who underwent chemotherapy alone.CONCLUSIONHigher survival rates and costs were found for patients exposed to modern treatments for advanced NSCLC. Cost-effectiveness thresholds definitions are warranted for managing costs, particularly in developing countries.